Transnational entrepreneurship, social networks, and institutional distance - Kaveh Moghaddam; Elzotbek Rustambekov; Thomas Weber; Sara Azarpanah (New England Journal of Entrepreneurship (NEJE), 2018)
Purpose - Transnational entrepreneurship can be considered a new stream of research where migrant entrepreneurship and international business research fields intersect. The purpose of this paper is to offer a theoretical framework to address the following research question: How do transnational entrepreneurs (TEs) develop their competitive advantage to succeed in a global market? Design/methodology/approach - Based on the strategic entrepreneurship approach and dynamic capability perspective, this paper suggests a theoretical framework to extend the understanding on how TEs may develop their competitive advantage to succeed in a global market. Findings - The suggested theoretical framework exhibits how the social ties of TEs affects their firm performance through the mediating effect of a bundle of two organizational processes (opportunity sensing and opportunity seizing) and the moderating effect of institutional distance between countries of origin and residence. Practical implications - TEs should not solely focus on their ethnic social ties. That is why this paper suggests that ethnic ties in the country of origin and the country of residence (COR) may lead to higher firm performance only if systematically used alongside nonethnic ties in the COR. Furthermore, it is crucial for TEs to understand the importance of dynamic capabilities in developing and sustaining their competitive advantage. Originality/value - Based on the strategic entrepreneurship approach, this paper suggests a social tie-based model of the dynamic capability to address the theoretical void in the transnational entrepreneurship literature. The linkage between social tie and performance which has been in a black box is examined in terms of how strong and weak social ties may affect different underlying processes of TEs' dynamic capabilities differently. In contrast to the common conceptualization of institutional distance as a negative moderator in international business literature, institutional distance is theorized as a positive moderator in the suggested theoretical model of transnational entrepreneurship.
Keywords: 650; Dynamic capability; Institutional distance; Social networks; Transnational entrepreneurship; Immigrant entrepreneur